Book Review Cucino V., Di Minin A., Ferrucci L., Piccaluga A., La Buona Impresa. Storie di start up per un mondo migliore, Il Sole 24 Ore, 2021 - Pencarelli, Tonino (Piccola Impresa / Small Business, 2022)
The review concerns a research work that illustrates a series of cases of Italian start-ups born with new purposes, attentive not only to the economic and financial aspects, but also to the social and environmental dimensions. The text highlights how in the context of youth entrepreneurship, often little known, there are value foundations for new models of capitalism, oriented by the desire to contribute to creating a better world. An interesting research, which demonstrates how a socially attentive entrepreneurial future is possible, also thanks to the active contribution of public institutions and universities.